Origin and Characteristics of the Shwetagun Deposit, Modi Taung-Nankwe Gold District and the Kunzeik and Zibyaung Deposits, Kyaikhto Gold District in Mergui Belt, Myanmar: Implications for Fluid Source and Orogenic Gold Mineralization - Hlaing, Myo Kyaw; Yonezu, Kotaro; Zaw, Khin; Myint, Aung Zaw; Aye, May Thwe; Watanabe, Koichiro (Frontiers in Earth Science, 2021)
The Mergui Belt of Myanmar is endowed with several important orogenic gold deposits, which have economic significance and exploration potential. The present research is focused on two gold districts, Modi Taung-Nankwe and Kyaikhto in the Mergui Belt comparing their geological setting, ore and alteration mineralogy, fluid inclusion characteristics, and ore-forming processes. Both of the gold districts show similarities in nature and characteristics of gold-bearing quartz veins occurring as sheeted veins, massive veins, stockworks to spider veinlets. These gold deposits are mainly hosted by the mudstone, slaty mudstone, greywacke sandstone, slate, and slaty phyllite of Mergui Group (dominantly of Carboniferous age). The gold-bearing quartz veins generally trend from NNE to N-S, whereas some veins strike NW-SE in all deposits. The gold-bearing quartz veins are mainly occurred within the faults and shear zones throughout the two gold districts. Wall-rock alterations at Shwetagun are mainly silicification, chloritization, and sericitization, whereas in Kyaikhto, silicification, carbonation, as well as chloritization, and sericitization are common. At Shwetagun, the gold occurred as electrum grains in fractures within the veins and sulfides. In Kyaikhto, the quartz-carbonate-sulfide and quartz-sulfide veins appeared to have formed from multiple episodes of gold formation categorizing mainly as free native gold grains in fractures within the veins or invisible native gold and electrum within sulfides. At Shwetagun, the ore minerals in the auriferous quartz veins include pyrite, galena, and sphalerite, with a lesser amount of electrum, chalcopyrite, arsenopyrite, chlorite, and sericite. In Kyaikhto, the common mineralogy associated with gold mineralization is pyrite, chalcopyrite, sphalerite, galena, pyrrhotite, arsenopyrite, marcasite, magnetite, hematite, ankerite, calcite, chlorite, epidote, albite, and sericite. At Shwetagun, the mineralization occurred at a varying temperature from 250 to 335°C, with a salinity range from 0.2 to 4.6 wt% NaCl equivalent. The Kyaikhto gold district was formed from aqueous–carbonic ore fluids of temperatures between 242 and 376°C, low to medium salinity (<11.8 wt% NaCl equivalent), and low CO2 content. The ore-forming processes of the Shwetagun deposit in the Modi Taung-Nankwe gold district and the Kyaikhto gold district are remarkably comparable to those of the mesozonal orogenic gold systems.